Severely low testosterone in males with COVID‐19: A case‐control study. (9th March 2021) - Salonia, Andrea; Pontillo, Marina; Capogrosso, Paolo; Gregori, Silvia; Tassara, Michela; Boeri, Luca; Carenzi, Cristina; Abbate, Costantino; Cignoli, Daniele; Ferrara, Anna Maria; Cazzaniga, Walter; Rowe, Isaline; et al.
Abstract: Background: Circulating androgens could have a relevant pathobiological role in clinical outcomes in men with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection (COVID‐19). Objectives: We aimed to assess: (a) circulating sex steroids levels in a cohort of 286 symptomatic men with laboratory‐confirmed COVID‐19 at hospital admission compared to a cohort of 281 healthy men; and (b) the association between serum testosterone levels (tT), COVID‐19, and clinical outcomes. Materials and Methods: Demographic, clinical, and hormonal values were collected for all patients. Hypogonadism was defined as tT ≤9.2 nmol/l. The Charlson Comorbidity Index (CCI) was used to score health‐significant comorbidities. Severe clinical outcomes were defined as patients either transferred to intensive care unit (ICU) or death. Descriptive statistics and multivariable linear and logistic regression models tested the association between clinical and laboratory variables and tT levels. Univariable and multivariable logistic regression models tested the association between tT and severe clinical outcomes. Results: Overall, a significantly lower levels of LH and tT were found in patients with COVID‐19 compared to healthy controls (all p  < 0.0001); conversely, healthy controls depicted lower values of circulating E2 ( p  < 0.001). Testosterone levels suggestive for hypogonadism were observed in 257 (89.8%) patients at hospital admission. In as many as 243 (85%) cases, hypogonadism was secondary. SARS‐CoV‐2 infection status was independently associated with lower tT levels ( p  < 0.0001) and greater risk of hypogonadism ( p  < 0.0001), after accounting for age, BMI, CCI, and IL‐6 values. Lower tT levels were associated with higher risk of ICU admission and death outcomes (all p  ≤ 0.05), after accounting for clinical and laboratory parameters. Conclusions: We unveil an independent association between SARS‐CoV‐2 infection status and secondary hypogonadism already at hospital admission, with lower testosterone levels predicting the most severe clinical outcomes.